A functional analytic method for the analysis of general partial differential equations - Sikolya, E. (Інститут програмних систем НАН України, 2006)
In this paper we give a short overview of operator semigroups. These objects are widely used for proving well-posedness of partial differential equations and for investigating qualitative properties of the solutions.